Perancangan Dan Implemetasi Sensor GPS Pada Sistem Navigasi Multirotor - Firdaus, Ramadan; Jatmiko, Didit Andri (Telekontran : Jurnal Ilmiah Telekomunikasi, Kendali dan Elektronika Terapan, 2020)
An autonomous navigation system is a system that is needed by robots to be able to move without human assistance, a drone is a type of flying robot that can move without a pilot in it. Autononomous navigation system on a drone is built by several sensors connected to a microcontroller to be processed into attitudes and movements of the drone to be able to navigate in accordance with the desired program. GPS can be used by a drone to find out the location of a drone on the surface of the earth because GPS can receive signals emitted by satellites and turn them into a location point that has value. Every part of the earth's surface is now almost reachable by satellite signals, so each location on the earth has different longitude and latitude coordinates. By using GPS, an autonomous system can be designed for drones to be able to move from one point on the surface of the earth to another point or the so-called waypoint system. In this autonomous navigation system made a long-distance navigation system for hexacopter drones, this system is made to determine the precision of the GPS sensor when used to navigate from one location to another. In carrying out its mission, the drone will be given several waypoints containing longitude and latitude values ​​that must be achieved by the hexacopter in running the mission. In research, the results show that a GPS-based navigation system can make navigation drones enter the desired area within a radius of 1 meter from the coordinates (setpoint) entered with the number of satellites obtained by GPS is 24 satellites, and out of a radius of 1 meter when the number of satellites is received are 19 satellites.